Designing UI/UX for Reading Games in Indonesian and English for Early Childhood Using the Human-Centered Design Method - Azzam, Abdullah; Ratnasari, Chanifah Indah (P3M Politeknik Negeri Bengkalis, 2024)
This research aims to design an educational game